Inhibition of proteoglycan synthesis by hydrogen peroxide in cultured bovine articular cartilage - Bates, Edna J.; Johnson, Colin C.; Lowther, Dennis A. (Biochimica et biophysica acta, 1985)
Oxygen-derived reactive species, generated enzymatically by the action of xanthine oxidase upon hypoxanthine, significantly inhibit proteoglycan synthesis by cultured bovine articular cartilage (Bates, E.J., Lowther, D.A. and Handley, C.J. (1984) Ann. Rheum. Dis. 43, 462–469). Here we extend these investigations and show, through the use of catalase and the specific iron chelator diethylenetriaminepentaacetic acid, that the active species involved is H 2O 2 and not the hydroxyl radical. Incubations of cartilage with H 2O 2 at concentrations of 1·10 −4 M and above are also inhibitory to proteoglycan synthesis. Subsequent recovery of the tissue is dependent upon the initial dose of xanthine oxidase or H 2O 2. Xanthine oxidase at 84 mU per incubation results in a prolonged inhibition of proteoglycan synthesis which is still apparent after 14 days in culture. Lower concentrations of xanthine oxidase (21–66 mU) are inhibitory to proteoglycan synthesis, but the tissue is able to synthesise proteoglycans at near normal rates after 3 days in culture. The inhibition of proteoglycan synthesis by 1·10 −4 M H 2O 2 is completely reversed after 5 days in culture, whereas 1·10 −3 M H 2O 2 results in a more prolonged inhibition. The synthesis of the proteoglycan core protein is inhibited, but the ability of the newly formed proteoglycans to aggregate with hyaluronic acid is unimpaired.